Effects of Exercise and Noise on Auditory Thresholds and Distortion-Product Otoacoustic Emissions - Hooks-Horton, Shannon; Geer, Susan; Stuart, Andrew (Journal of the American Academy of Audiology, 2001)
Differences in auditory thresholds and distortion-product otoacoustic emission (DPOAE) levels were investigated as a function of gender, ear, frequency, and experimental condition: quiet sedentary activity, exercise, noise, and exercise and noise combined. In general, participants displayed significant elevations in auditory thresholds of approximately 6 to 13 dB following the two conditions employing noise exposure. There were no significant differences in either auditory threshold differences before and following the quiet and exercise conditions or between the noise-alone and combined exercise and noise conditions. Participants also displayed significant reductions in DPOAE levels of approximately 6 to 7 dB following the two conditions employing noise exposure. The findings also showed no gender or ear effects on auditory threshold or DPOAE level differences. Further, there was no evidence of a synergistic combination of exercise and noise on auditory function as revealed by changes in hearing threshold or DPOAE levels.Abbreviations: DPOAE = distortion-product otoacoustic emissions, TTS = temporary threshold shift
Keywords: Auditory threshold; distortion-product otoacoustic emissions; exercise; noise